An evaluasion of the course book powerbase-pre-intermediate" Dong A University of technology = Đánh giá giáo trình “Powerbase – Pre intermediate” đang được sử dụng tại khoa Quản trị Kinh doanh Trường Đại học Công Nghệ Đông Á. M.A Thesis Linguistics : 60 1 - Vũ, Thị Hoài (University of Languages and International Studies, 2017)
44 p. + CD-ROM